2019
DOI: 10.1021/jacs.8b13871
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Moieties Bestow Fast-Folding and Hyperstability on Collagen Triple Helices

Abstract: Trans amide bonds and fast cis–trans isomerization of Xaa-Pro bonds are crucial for the stability and folding rate of collagen, the most abundant protein in mammals. Here, we explored the effect of pendant hydrophobic moieties on the folding and stability of collagen triple helices. Kinetic studies with a series of collagen model peptides showed that a local hydrophobic environment accelerates cis–trans isomerization to an extent that thermally induced unfolding and folding of the collagen triple helix take pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…This is of interest from both fundamental and applied points of view. Indeed, this work also aims to provide useful insights into collagen protein engineering. To achieve our goals, we rely on computer simulations, based on DFT and HF theories (see Computational Methods and the Supporting Information for further details). We have analyzed seven collagen helices, which differ for the amino acid triplet rotational angle (α), i.e., α = 90°, 72°, 60°, 51.4°, 40°, 36°, and 0°.…”
mentioning
confidence: 99%
“…This is of interest from both fundamental and applied points of view. Indeed, this work also aims to provide useful insights into collagen protein engineering. To achieve our goals, we rely on computer simulations, based on DFT and HF theories (see Computational Methods and the Supporting Information for further details). We have analyzed seven collagen helices, which differ for the amino acid triplet rotational angle (α), i.e., α = 90°, 72°, 60°, 51.4°, 40°, 36°, and 0°.…”
mentioning
confidence: 99%
“…However, the ethoxy groups in Ac‐ (EtO) 2 ‐ProM1 ‐OMe were found to be radially oriented, pointing away from the triple helix axis. In addition to existing methods for triple‐helix functionalization, the (HO) 2 ‐ProM1 scaffold might be used for double functionalization by O‐alkylation. In conclusion, the steric demand of the linker group was determined to be crucial for the thermal stability of ProM‐modified CMPs.…”
Section: Resultsmentioning
confidence: 99%
“…As steric repulsion within the triple helix could explain this result, [39] the DFT-optimized structures of Ac-(EtO) 2 -ProM1-OMe and Ac-(EtO) 2 -ProM2-OMe were aligned with (PPG) 10 to describe the steric situation in the corresponding collagen model peptides.T he alignments (Figure 7) showed that the ethoxy groups in Ac-(EtO) 2 -ProM2-OMe indeed clash with apreceding carbonyl group of the same strand and ap roline ring of an eighboring strand. However,t he ethoxy groups in Ac-(EtO) 2 -ProM1-OMe were found to be radially oriented, pointing away from the triple helix axis.Inaddition to existing methods for triple-helix functionalization, [41][42][43] the (HO) 2 -ProM1 scaffold might be used for double functionalization by O-alkylation. In conclusion, the steric demand of the linker group was determined to be crucial for the thermal stability of ProM-modified CMPs.…”
Section: Analysis Of Structure-stability Relationshipsmentioning
confidence: 99%